Massive Star Formation in Overdense Regions of the Early Universe - John Regan (The Open Journal of Astrophysics)
Both the origin of, and the population demographics of, massive black holes (MBHs) remains an open question in modern day astrophysics. Here we introduce the _BlackDemon_ suite of cosmological simulations using the _enzo_ code. The suite consists primarily of three, high resolution, distinct regions, each with a side length of 1 $h^{-1}$ Mpc. Two of the regions evolve within a larger overdense region while the other evolves within a more 'normal' region. The simulation suite has spatial and mass resolution capable of resolving the formation of the first galaxies and MBHs within each region. We report here, as the first in a series of papers, the evolution of the simulation suite up to the point where star formation has commenced in each region and for 2 Myr after the onset of star formation. Within these environments the masses of the first objects to form have masses between approximately 100 M${\mathstrut}_{\odot}$ and $10^4 \ M_{\odot}$. The larger mass objects form due to both major mergers, which trigger rapid mass inflow to the centre of the halo, and also through multiple minor mergers which allows the host halo to grow to close to the atomic cooling threshold. In both scenarios the initially very high accretion rates quickly grow the objects to close to $10^4 \ M_{\odot}$. However, the accretion halts after less than 50,000 years due to gas starvation. The final fate of these objects in terms of fragmentation and subsequent fragment mergers cannot be deduced at our current resolution. In the case where fragmentation is mild such objects are likely to form super-massive stars before contracting to the main sequence evolving into a massive population III star and subsequently a MBH.